Befriending Our Desires : Third Edition - Sheldrake, Philip (Book collections on Project MUSE., 2016)
Desire is at the heart of what it is to be human. The power of desire, while embodied and sensuous, is God-given and the key to all human spirituality. Humanity is blessed with a deep longing that is infinite in extent and can only ultimately be satisfied in God. Befriending Our Desires portrays the intimate connection between desire and the spiritual journey. Drawing on Hebrew and Christian Scriptures, Christian spiritual classics (with some reference to Buddhist spirituality), poetry, and other literature, plus personal and pastoral experience, Philip Sheldrake explores the role of desire in relation to God, prayer, sexuality, making choices, and responding to change.